DIAGNOSTIC VALUES OF BIOCHEMICAL MARKERSIN ASPHYXED NEWBORNS WITH PROVEN SEPSIS - Sofijanova, Aspazija; Timovska, Silvana Naunova; Mangjukova, Hristina; Shuperliska, Elizabeta; Jordanova, Olivera; Bojadzieva, Sonja (Journal of Morphological Sciences; Vol 3 No 2 (2020): JMS, 2020)
Introduction: The aim of this study was to investigate the predictive values of biochemical parameters, including Procalcitonin (PCT), as an early diagnostic and prognostic marker for sepsis in asphyxed newborns with proven sepsis. Materials and Methods: This study was designed as a prospective study, where we included 110 (M:F=67:43) newborns with proven sepsis hospitalized in the Intensive Care Unit at the PHI University Children’s Hospital – Skopje.PCT and CRP,WBC one serum blood sample was obtained from each patient at the 24h at admission, as well asday 3 and day 7. Procalcitoninlevels were measured by using an immunoassay system Vidas, based on the Enzyme Linked Fluorescent Assay (ELFA) principles. Results :  The newborns with proven sepsis have been divided into two groups. The first group included 50 proven septicpreterm newborns with a positive blood culture and the second group included 50 proven sepsis full-term newborns.We isolated forty two that had two or three bacteria at the same time. The identified bacteria included  Staphylococcus aureus  (n=56) mecA , Streptococcus  (n=6),  Acinetobacter baumannii  (n=18),  Serratia  marcescens  (n=9) and  Entrobacteriaceae  (n=31), Candida albicans (n= 1), Candida parapsilosis (n=1).Statistical analysis confirmed significantly different values ​​of PCT in the analyzed time period in preterm newborns with proven sepsis p<0.001.Statistical analysis confirmed significantly different values ​​of PCT in the analyzed time period in newborns with proven sepsis with asphyxia p<0.001. Conclusion: The levels of PCT have important clinical significance in predicting the prognosis of asphyxed newborns with sepsis, to prevent the development of severe sepsis and septic shock. Keywords:sepsis,C-reactive protein,procalcitonin PCT, asphyxed newborns